Pengaruh Penyuluhan terhadap Tingkat Pengetahuan dan Sikap Santri dalam Pencegahan Covid-19 pada Pondok Pesantren ZIIS Cilongok Banyumas - Anggina Lestari; Mia Kusmiati; M. Fitriandi Budiman (Bandung Conference Series: Medical Science, 2022)
Abstract. Corona Virus Disease 2019 (COVID-19) is a global health problem and has become a global pandemic. Efforts that can be made in preventing COVID-19 are to carry out health promotion activities, one of which is counseling. Counseling to provide education about preventing the transmission of COVID-19 is very important among students as a prevention effort in Islamic boarding schools. The purpose of this study was to determine the difference in the effect of the level of knowledge and attitudes of Islamic boarding school students in Banyumas in preventing COVID-19 before and after counseling. This research design is pre-experimental and uses pretest-posttest design. The research population of students at the Ziis Islamic Boarding School, Purwokerto Banyumas for the 2020/2021 academic year, was taken as many as 136 students with a simple random sampling technique. Data were taken using a questionnaire conducted before and before being given counseling. Univariate data analysis describes levels and attitudes in preventing Covid-19, and bivariate using paired statistical tests to determine differences in knowledge and attitudes of Islamic boarding school students in Banyumas in preventing COVID-19 before and before counseling. Based on the research, the knowledge of respondents before being given counseling was still in the less category, namely 40 people (29.4%) and after being given counseling there are 7 people (5.1%) in the less category. The attitude of respondents before being given counseling was still in the negative category, namely 32 people (23.5%) and after counseling, there was no more. It can be concluded that COVID-19 counseling influences the level of knowledge and attitudes of students in preventing COVID-19 at Islamic boarding schools in Banyumas. Abstrak. Corona Virus Disease 2019 (COVID-19) merupakan masalah kesehatan dunia dan menjadi pandemi global. Upaya yang dapat dilakukan dalam pencegahan COVID-19 adalah dengan melakukan kegiatan promosi kesehatan, salah satunya adalah kegiatan penyuluhan. Penyuluhan untuk memberikan edukasi mengenai pencegahan penularan COVID-19 sangat penting di kalangan santri sebagai upaya pencegahan di pondok pesantren. Tujuan penelitian ini adalah mengetahui perbedaan pengaruh tingkat pengetahuan dan sikap santri pondok pesantren di Banyumas dalam pencegahan COVID-19 sebelum dan sesudah dilakukan penyuluhan. Rancangan penelitian ini pre-experimental dan menggunakan desain pretest-posttest. Populasi penelitian santri di pondok pesantren Ziis Purwokerto Banyumas tahun ajaran 2020/2021 yang diambil sebanyak 136 santri dengan teknik simple random sampling. Data diambil menggunakan kuesioner yang dilakukan sebelum dan sesudah diberikan penyuluhan. Analisis data univariat menggambarkan tingkat pengetahuan dan sikap dalam pencegahan Covid-19, dan bivariat menggunakan uji statistik paired t-test untuk mengetahui perbedaan tingkat pengetahuan dan sikap santri pondok pesantren di Banyumas dalam pencegahan COVID-19 sebelum dan sesudah dilakukan penyuluhan. Berdasarkan hasil penelitian, pengetahuan responden sebelum diberikan penyuluhan ada yang masih pada kategori kurang yaitu 40 orang (29.4%) dan setelah diberikan penyuluhan terdapat 7 orang (5.1%) dalam kategori kurang. sikap responden sebelum diberikan penyuluhan ada yang masih pada kategori negatif yaitu 32 orang (23.5%) dan setelah diberikan penyuluhan sudah tidak ada lagi. Dapat disimpulkan bahwa penyuluhan COVID-19 memiliki pengaruh terhadap tingkat pengetahuan dan sikap santri dalam pencegahan COVID-19 pada pondok pesantren di Banyumas.